2008
DOI: 10.1182/blood-2007-03-078535
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib down-regulates the cell-surface expression of HLA class I and enhances natural killer cell–mediated lysis of myeloma

Abstract: IntroductionMultiple myeloma (MM) is a prototypic B-cell malignancy with overall survival varying from a few months to more than 15 years with melphalan-based autologous stem cell transplantation. 1 It is well established that patients with abnormal, especially hypodiploid karyotypes, and high lactic dehydrogenase have a worse prognosis. 2 Recently, we have reported that approximately 13% of MM patients have a high-risk prognostic score defined by the differential expression of 70 key genes, many of which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 53 publications
9
128
2
Order By: Relevance
“…[25][26][27][28] The activity and survival of human NK cells may be further enhanced by using IL15 which has not yet been applied in human trials, but has been shown to expand NK cell numbers in non-human primates. 29 Bortezomib could be utilized to down-regulate HLA class I molecules, 30 increase TRAILmediated apoptosis and up-regulate DNAM-1 and NKG2D ligands. [31][32][33] A phase II clinical trial has been initiated at our institution which examines the therapeutic effect of both allogeneic and autologous exp-NK cells for relapsed/refractory GEP-defined high-risk MM.…”
Section: Tk Garg Et Almentioning
confidence: 99%
“…[25][26][27][28] The activity and survival of human NK cells may be further enhanced by using IL15 which has not yet been applied in human trials, but has been shown to expand NK cell numbers in non-human primates. 29 Bortezomib could be utilized to down-regulate HLA class I molecules, 30 increase TRAILmediated apoptosis and up-regulate DNAM-1 and NKG2D ligands. [31][32][33] A phase II clinical trial has been initiated at our institution which examines the therapeutic effect of both allogeneic and autologous exp-NK cells for relapsed/refractory GEP-defined high-risk MM.…”
Section: Tk Garg Et Almentioning
confidence: 99%
“…Encouraging preliminary results of these studies prompted us to evaluate the potential value of daratumumab in lenalidomide-and bortezomibrefractory multiple myeloma patients, who have a very poor prognosis at present. We hypothesized that, despite the drug resistance of the malignancy, the immune system of these patients could still respond to the previously described immunomodulatory effects of lenalidomide (11)(12)(13)(14) and bortezomib (15,16). Therefore, we now evaluated daratumumab alone or in combination with lenalidomide or bortezomib as a potential therapy for lenalidomide-and bortezomib-refractory patients.…”
Section: Introductionmentioning
confidence: 99%
“…PRDXs are currently known to possess six mammalian isoforms. Although their individual roles in cellular redox regulation and antioxidant protection are quite distinct, they all catalyze peroxide reduction to balance cellular H 2 O 2 levels essential for signaling and metabolism (Shi et al 2008). Besides their cytoprotective antioxidant function, PRDXs appear to play a role in cell proliferation, differentiation, immune response, protection of oxidant-sensitive proteins, regulation of cellular H 2 O 2 , control of apoptosis, and processes involving redox signaling (Shi et al 2008).…”
Section: Introductionmentioning
confidence: 99%